Effect of Family Support and Peer Support on The Quality of Life of The Elderly: A Path Analysis Evidence from Jember, East Java - Malinda Capri Nurul Satya; RB. Soemanto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Indonesia is one of the countries with an elderly population by >7%. It may increase every year. The number of elderly people will increase globally and lead to several problems such as health, psychological, social, and economic problems. Other psychological problems experienced by the elderly are loneliness due to loss of spouse, separation from family, and loss of peers. This study aimed to analyze the effect of family support and peer support on the quality of life of the elderly.Subjects and Method: This was a cross-sectional study carried out at of Tresna Werdha social service, in Wuluhan, Jember, East Java, from August to September 2019. A sample of 200 elderly aged >60 years old was selected by fixed exposure sampling. The dependent variable was quality of life. The independent variables were education, healthy behavior, family income, family support, peer support, and residence. The study was collected by questionnaire and analyzed by path analysis.Results: Good quality of life on the elderly increased with healthy behavior (b= 1.06; 95% CI 0.25 to 1.87; p= 0.010), education ≥Senior high school (b= 1.33; 95% CI 0.37 to 2.29; p= 0.007), family income ≥Rp 2,170,000 (b= 1.59; 95% CI 0.17 to 3.02; p= 0.028), strong family support (b= 1.93; 95%CI 0.47 to 3.39; p= 0.010), strong peer support (b= 1.18; 95%CI= 0.21 to 2.16; p=0.017), and residence at home (b=1.46; 95% CI 0.26 to 2.65; p=0.017).Conclussion: Good quality of life on the elderly increased with healthy behavior, education ≥Senior high school, high family income, strong family support, strong peer support, and residence at home.Keywords: quality of life, family support, peer supportCorrespondence: Malinda Capri Nurul Satya. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: malindacaprins@gmail.com. Mobile: 085236936546Journal of Health Promotion and Behavior (2019), 4(3): 159-169https://doi.org/10.26911/thejhpb.2019.04.03.01